Antibacterial Activities Test of Combination of Ethanolic Extract of Betel Leaves (Piper betle L.) and Basil Leaves (Ocimum basilicum L.) Against Staphylococcus aureus - Junie Suriawati; Patimah Patimah; Siti Rahayu Rachmawati (Politeknik Kesehatan Kemenkes Jakarta II, 2018)
Betel leaf extract and basil leaf extract contain phenol compounds, safonin, flavonoids, tannins, and essential oils that act as antibacterials. Skin is very susceptible to infection or other skin diseases one of which is caused by Staphylococcus aureus bacteria. This research needs to be done to test the antibacterial activity of ethanol extract of green betel leaf, basil leaf and combination of both extracts to S. aureus. The process of extraction of betel leaf and basil leaves was done with 96% ethanol solvent using maceration method. The combinations used in the sample solution were the concentration of ethanol extract of green betel leaf (0%, 15%, 30%, 45%, 60%, 75%) and basil leaf extract (0%, 15%, 30%, 45%, 60 %, 75%). Furthermore, the antibacterial activity was tested for S. aureus with well diffusion method. The data obtained were tested statistically using Anova and Duncan's advanced test. The result of statistical analysis showed difference of drag zone (p <0,05) between various concentration of ethanol extract of green betel leaf, basil leaf and combination of both extracts to S. aureus. The smallest resin zone of ethanol extract of betel leaf and ethanol extract of basil leaves is at 0% concentration (S0 and K0) and highest at 75% concentration (S5 and K5). While the smallest zone of inhibition for the combination of ethanol extract of betel leaf and ethanol extract of basil leaves at concentration S0K0, S0K1 and S0K2 is 0 mm and highest at S5K5 concentration is 31,3 mm. The higher concentration of betel leaf extract, basil leaf extract and the combination of the two extracts, the inhibition of diameter zone will be better. It can be concluded that the combination of betel leaf extract and basil leaf extract has the ability to inhibit the growth of S. aureus better than single extract.